2019
DOI: 10.1108/apjml-03-2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sport involvement, perceived event prestige, and the intention to attend annual spectator events

Abstract: Purpose The purpose of this paper is to examine the relationship between sport involvement, perceived event prestige and attendance intention of annual sporting events. In addition, it examines the moderating effects of gender and past experience on the proposed model. Design/methodology/approach Data were collected, using an on-site survey, from spectators (n=349) who attended the men’s or women’s basketball tournaments of the 2016 William Jones Cup held in Taiwan. Findings The results showed that perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…Belli et al, (2016) found a significant difference in favor of physical education and sports teaching department students in their study on sports sciences faculty students' football support. It can be said that the fans support their teams by buying tickets and licensed products to show their loyalty to their teams (Chiu et al, 2019). Dwyer et al (2015) argue that fans committed to their team can serve as "efangelists" in actively participating in team-centered interactions and passionately spreading beliefs about the team to other people.…”
Section: Discussionmentioning
confidence: 99%
“…Belli et al, (2016) found a significant difference in favor of physical education and sports teaching department students in their study on sports sciences faculty students' football support. It can be said that the fans support their teams by buying tickets and licensed products to show their loyalty to their teams (Chiu et al, 2019). Dwyer et al (2015) argue that fans committed to their team can serve as "efangelists" in actively participating in team-centered interactions and passionately spreading beliefs about the team to other people.…”
Section: Discussionmentioning
confidence: 99%
“…Koo and Lee (2019) conceptualized sport involvement as anticipated interest and individual significance of sports to a person. Along these lines, sport involvement is bound to be a piece of enduring involvement (or internal sources of personal relevance) since one commonly has a steady enthusiasm for sports and does not lose this enthusiasm very easily (Chiu et al , 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, sport fans with different levels of attitudinal and behavioral loyalty may develop different perceptions towards their favorite teams [47,53]. According to the psychological continuum model proposed by Funk and James [47], sport fans' involvement progressively develops with corresponding behaviors toward their favorite teams [54]. In a similar vein, loyalty level plays an essential role in determining sport fans' price sensitivity and latitude of price acceptance [55].…”
Section: Sport Fan Loyaltymentioning
confidence: 99%
“…For example, teams can launch various activities or events on different social media platforms to attract indifferent fans. Doing so can motivate indifferent fans to be more engaged and involved in team activities, which further enhance their loyalty levels [54].…”
Section: Practical Implicationmentioning
confidence: 99%